Linum trigynum - Tajima's D estimates per population - Postel, Zoe; Fracassetti, Marco; Slotte, Tanja; Gutiérrez-Valencia, Juanita; Zervakis, Panagiotis-Ioannis; Bunikis, Ignas; Soler, Lucile; Losvik, Aleksandra; Desamore, Aurelie; Hughes, P. William; Mehrabi, Sara; Laenen, Benjamin; et al. (Stockholm University, 2024)
Whole genome Tajima's D estimates for individuals of all population of L. trigynum per 100 kb windows.

It is part of this article: Gutiérrez-Valencia, J., Zervakis, P. I., Postel, Z., Fracassetti, M., Losvik, A., Mehrabi, S., ... & Slotte, T. (2024). Genetic causes and genomic consequences of breakdown of distyly in Linum trigynum. Molecular Biology and Evolution, msae087. https://doi.org/10.1093/molbev/msae087

Estimations were done using vcftools v.0.1.16 on a filtered vcf file.

File's descriptions:


- CHROM = the chromosome's name

- START = the start position of the 100 kb window

- END = the end position of the 100 kb window

- TajimaD = the estimated value of Tajima's D for that window



List of the populations:


- population 01

- population 03

- population 04

- population 06

- population 07

- population 08

- population 10

- population 11
Keywords: Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi